Foreign direct investment location decision and pollution: evidence from Malaysia - Abdul Hamid Jaafar,; Md. Elias Hossain, (Penerbit Universiti Kebangsaan Malaysia, 2007)
There is considerable development gap between regions in Malaysia. The objective of this paper is to examine the impact of regional environmental pollution condition on foreign direct invesbnent location decision across regions in Malaysia. In this study, several regional environmental variables are included as determinants of foreign direct investment location decision. The study uses state level data from 1995 to 2004 on a random eflects panel regression model. Results ffom this study indicate that while positive economic circumstances attract foreign direct investment, negative environmental conditions, especially air pollution, serve as push factors. This finding suggests that local regions should improve their environmental condition in order to stand a better chance of attracting foreign as well as local investment.